1H and 19F FFC-NMR of catalyst layer materials for polymer electrolyte membrane fuel cells - Yamaguchi, Makoto; Ohira, Akihiro (Diffusion Fundamentals, 2013)
1H and 19F spin lattice relaxation rates of catalyst layer materials (CLM) of polymer electrolyte membrane fuel cells were measured by the fast field cycling (FFC) method. In contrast to ionomer membranes, 1H relaxation rates of adsorbed water in both platinum-Ketjen black (Pt-KB) catalyst powder and CLM were strongly dependent on Larmor frequency approximated by a power law due to the strong surface interaction of adsorbed water. The difference in the frequency dependence in the Pt-KB and the CLM was attributed to higher acidity of the CLM.